Engineering geology and geomorphology of glaciated and periglaciated terrains : engineering group working party report - Griffiths, James S., Dr; Martin, C. J. (Geologist) (Geological Society engineering geology special publication ;, 2017)
The Engineering Group of the Geological Society Working Party brought together experts in glacial & periglacial geomorphology, Quaternary history, engineering geology & geotechnical engineering to establish best practice when working in former glaciated & periglaciated environments. The Working Party addressed outdated terminology & reviewed the latest academic research to provide an up-to-date understanding of glaciated & periglaciated terrains. This transformative, state-of-the-art volume is the outcome of five years of deliberation & synthesis by the Working Party. This is an essential reference text for practitioners, students & academics working in these challenging ground conditions. The narrative style, & a comprehensive glossary & photo-catalogue of active & relict sediments, structures & landforms make this material relevant & accessible to a wide readership.